Annual pollen spectrum in the air of Palma de Mallorca (Balearic Islands, Spain) - Boi, M.; Llorens, L. (AEROBIOLOGIA, 2013)
This aeropalynological study documented the pollen of 13 taxa with the highest concentration in the air of Palma de Mallorca during the years 2004-2010, using a Hirst-type volumetric spore trap. The taxa were Cupressaceae, Olea europaea, Platanus hispanica, Pinus spp., Parietaria judaica, Urtica membranacea, Quercus ilex, Poaceae, Chenopodiaceae/Amaranthaceae, Plantago spp., Castanea sativa, Pistacia lentiscus and Betula spp. These taxa accounted for 91.85 % of the total annual pollen recorded during the period. The mean annual pollen index was 20,027. The highest pollen counts occurred in February-June, representing 88.74 % of the annual total collected. Every year, there was a substantial increase in the concentration and types of pollen from March to May, followed by a decrease from July to January. The maximum annual total pollen count was recorded in 2005 with 25,870 and the minimum in 2009 with 14,726. The mean daily average pollen concentration count showed a declining trend over the study period. With respect to seasonal phases analysed, the later phase of the pollen season is more variable than the beginning. To observe the overall dynamics of the different pollen types better, a pollen calendar was established for Palma de Mallorca. The pollen calendar had typical Mediterranean features and is a useful tool for allergological and botanical awareness.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Aerobiology; Allergenic pollen; Palma de Mallorca; Pollen calendar

Variations in Quercus ilex chloroplast pigment content during summer stress: involvement in photoprotection according to principal component analysis - Llorens, L.; Aranda, X.; Abadia, A.; Fleck, I. (FUNCTIONAL PLANT BIOLOGY, 2002)
We examined chloroplast pigment variation in holm oak (Quercus ilex L.) leaves for two periods under two climatic conditions, at midday during summer. We compared variation between control (unburned) plants and plants burned the preceding summer, since post-fire resprouts show higher photosynthetic rates and lower thermal energy dissipation. Principal component (PC) analysis was performed on nine pigment-content variables for the two periods separately. Two PC factors (PC1 and PC2) explained 83 and 84% of the variance of the data for each period. In both periods, PC 1 was marked by positive loading of pigments associated with light absorption or structural function namely neoxanthin, lutein, beta-carotene, chlorophyll a, and chlorophyll b. These pigments were only affected by leaf age. In contrast, PC2 was marked by high loadings of xanthophyll-cycle pigments (associated with photoprotection), and lutein-5,6-epoxide. Leaf content of these pigments was affected by climatic conditions. In the situations considered in PC analysis (leaf types, periods), the lutein-5,6-epoxide content presented a variation pattern similar to that of violaxanthin, and was significantly correlated with thermal dissipation of excess energy (represented by non-photochemical quenching or NPQ). These results suggest a relationship of lutein and lutein-5,6-epoxide with photoprotection.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: 6-epoxide; chlorophyll; lutein-5; photoprotection; Principal component analysis

Quercus ilex resprouts after fire: response to photoinhibition. - Aranda, X.; Hogan, K.; Llorens, L.; Fleck, I. (PLANT PHYSIOLOGY, 1997)
The study was located on Serra del Garraf mountains, Barcelona, NE Spain, overlooking the Mediterranian sea at 530 m. On August 1995 a wild fire consumed 100 hectares of the forest. In spring 1996 four plots were set (100 x
APSAPSThe following values have no corresponding Zotero field: pub-location: 15501 MONONA DRIVE, ROCKVILLE, MD 20855 publisher: AMER SOC PLANT PHYSIOLOGISTS
Keywords: Mediterranean; wild fire